Η περιοδεία του Μητροπολίτου Βεροίας Δανιήλ (1769-1799;) στα χωριά της επαρχίας Βεροίας, κατά ανέκδοτο κώδικα της ιεράς Μητροπόλεως Βεροίας, Ναούσης και Καμπανίας. ATHANASIOS G. VOUDOURIS, The Tour of Metropolitan of Veria Daniel (1769-1799;) at the vill - Βουδούρης Αθανάσιος Γ. (Μακεδονικά, 2011)
Metropolitan of Veria Daniel’s (1769 – 1799?) tour is being known by anunpublished for the moment code of Holy Metropolis of Veria, Naousa andKabania. Unfortunately, we don’t know much about the life and the action ofthe Metropolitan. One of the most important points of his action is the specialinterest that he had shown for the awakening of the enslaved Greeks and theflourishing of education in his region.The particular tour is divided into three phases. Every village he hadvisited, metropolitan Daniel, performed religious ceremonies. The purpose ofthe tour was on one hand to gather money for his own needs and theMetropolis’ which was called «Archbishopric allowance» and on the other handwas the ethnic and spiritual awakening of the believers. By this tour, weobtain important information about the economical status of bishops of Veriaregion in the second half of the 18th century, the economical status and thepopulation of the region at this period, the composition of the region itselfbefore the 1821 rebellion. It is also presented the situation of villages of Veriabefore and after the 1821 rebellion.